Increasing profitability and price effectiveness of reseller business in fresh vegetables marketing in Mataram City, Indonesia - Tajidan, Tajidan; Fernandez, Edy; Nabilah, Sharfina; Yusuf, Muhammad; Effendy, Effendy (International Journal of Innovative Research and Scientific Studies, 2025)
The reseller business in online marketing has been widely discussed in international journals. In this article, the author measures retailers’ performance and finds solutions to increase profits and assess the effectiveness of fresh vegetable prices at the consumer level. The research was carried out in Mataram City at all traditional markets using a descriptive-explanatory method. All resellers and non-reseller merchants were designated as respondents. Data were collected through observation, surveys, and in-depth interview techniques. The data were analyzed using mathematical equations and descriptive statistics. The results show that the reseller method can increase selling prices and profits. An increase in the selling price can enhance profitability. A price effectiveness of 0.6684 indicates that every one percent increase in price can raise profits by 0.6684 percent. The increase in vegetable prices is effective in boosting resellers’ profits. An increase in the selling price of vegetables should be accompanied by an improvement in quality and services to the consumers.